2011
DOI: 10.1097/ss.0b013e31822391a6
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Availability to Corn From Dairy Manures and Fertilizer in a Calcareous Soil

Abstract: The expansion of the dairy industry in southern Idaho has led to increased application of manures to meet crop nutrient demands that can alter the uptake pattern of both macronutrients and micronutrients. A greenhouse study was conducted to determine the effects of dairy manure, composted dairy manure, and fertilizer (monoammonium phosphate) application on soil test phosphorus (P), microbial activity, and nutrient uptake by silage corn (Zea mays). Two Portneuf soils, having either a low or high soil test P con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 31 publications
(36 reference statements)
3
22
0
Order By: Relevance
“…The DMA increased CEC of mudflat soil, probably due to increasing soil OM content [28,29]. In this study, the pH of mudflat soil did not show significant variation between treatments, which is in agreement with findings by Leytem et al [30]. Previous studies found soil pH increased with dairy manure application in alum shale soil [12] and Rosholt soil [31], and did not change in Plano soil [31].…”
Section: Discussionsupporting
confidence: 82%
“…The DMA increased CEC of mudflat soil, probably due to increasing soil OM content [28,29]. In this study, the pH of mudflat soil did not show significant variation between treatments, which is in agreement with findings by Leytem et al [30]. Previous studies found soil pH increased with dairy manure application in alum shale soil [12] and Rosholt soil [31], and did not change in Plano soil [31].…”
Section: Discussionsupporting
confidence: 82%
“…Warman and Cooper (2000) reported lower Mn forage tissue concentrations in compost treatments than fertilizer treatments. Leytem et al (2011) also documented decreased Mn uptake for corn grown on manure and compost‐treated soils in comparison to P fertilizer. Leytem et al (2011) suggested that the decrease in Mn tissue concentration may have been attributed to Mn complexation by organic acids in the manure.…”
mentioning
confidence: 93%
“…Parsons et al (2007) found significant reductions in Ca uptake by wheat receiving manure applications in comparison to fertilizer or an unamended control. The authors noted that Ca uptake may have been hindered by competition with K. Leytem et al (2011) also found reduced Ca uptake in corn with increasing dairy manure application rates. In addition to cation competition, the authors suggested that the reduction in Ca uptake on manure‐treated soils may also be related to the formation of Ca‐phosphate precipitates.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, there is a need to find an appropriate soil management strategy that could reduce inorganic fertilization and enhance soil fertility. Nutrient-enriched manure is commonly applied as a cost-effective alternative to inorganic fertilizers (Moore et al, 2014;Leytem et al, 2011). Manure treatment in calcareous soils could be a promising strategy for maintaining soil OM and improve soil physical and biochemical properties (Zhao et al, 2009).…”
Section: Introductionmentioning
confidence: 99%